Research methodology and tools in physical education and sports: conceptual basics of Master education curriculum - Zakirova, A. F. (Theory and Practice of Physical Culture, 2017)
The study offers conceptual basics for the Research Methodology and Tools in Physical Education and Sports curriculum for a master education course, with a special emphasis on the challenges of the research methodology learning in the master education course. We considered the paradigm-related disharmonies and contradictions in the process of natural-scientific and humanitarian components of the research technology being integrated. Of special interest were the theoretical knowledge integration related limitations in the general world outlook aspect - when the didactic principles and educational process goals are set and, to a lesser degree - in the theoretical material selection process driven by the interdisciplinary connections; and it is also noted that the modern research methods applied in humanitarian sciences are still underemployed in actual practices. The study overviews benefits of the humanitarian research paradigm driven by every personality value and meaning of every individual life event being highly appreciated. The study data and analyses were used to outline the potential ways to improve the academic progress in the research domain by theoretically grounded and systemic synergies in the research process with the classical and new research approaches being combined; and demonstrated potential benefits of hermeneutical technologies for the problem-solving in the physical culture and sports sector.